PERANCANGAN BUKU FOTOGRAFI KULINER KHAS CHINA DI MALANG SEBAGAI INFORMASI BAGI GENERASI ZOOMERZ (USIA 13-25 TAHUN) - Suyono, Kevin Jonathan; Nugroho, Didit Prasetyo; Prasetya, Bintang Pramudya Putra (Ma Chung Press, Universitas Ma Chung, 2025)
The city of Malang offers a wide variety of culinary delights. As time progresses and innovation increases, the existence of Chinese culinary culture continues to adapt to the locally available ingredients in Indonesia. Consequently, ingredients are adjusted to distinguish between non-halal and halal options, to suit the preferences of Indonesia’s majority population. This adaptation of ingredients not only supports cultural sensitivity but also enhances the diversity of Indonesia’s culinary heritage. Today’s younger generation is increasingly exploring various types of Chinese cuisine and is actively seeking information about which dishes are halal or non-halal. Chinese cuisine itself includes both vegetarian and non-vegetarian dishes. However, there is still a lack of understanding among some members of the younger generation regarding the difference between vegetarian and non-vegetarian food. Therefore, an informative medium is needed to both introduce Chinese cuisine and provide background on how it came to Indonesia. The design method used in this project is the creative communication design method, which involves collecting data through qualitative research. This photography essay book is designed in a 22 x 18 cm format, printed in full color a total of 95 pages, and features a hardcover with a matte lamination finish. The conclusion of this design project is the creation of a photography essay book that effectively introduces a variety of Chinese dishes through a modern yet authentic visual concept, presented with compelling photography and narrative text. Supporting media includes a brain-teasing card game, keychains, bookmarks, tent cards, t-shirts, posters, stickers, and a tripod banner.